Anti-Inflammatory Cytokines: Important Immunoregulatory Factors Contributing to Chemotherapy-Induced Gastrointestinal Mucositis. (2nd September 2012) - Sultani, Masooma; Stringer, Andrea M.; Bowen, Joanne M.; Gibson, Rachel J.
Abstract : "Mucositis" is the clinical term used to describe ulceration and damage of the mucous membranes of the entire gastrointestinal tract (GIT) following cytotoxic cancer chemotherapy and radiation therapy common symptoms include abdominal pain, bloating, diarrhoea, vomiting, and constipation resulting in both a significant clinical and financial burden. Chemotherapeutic drugs cause upregulation of stress response genes including NF κ B, that in turn upregulate the production of proinflammatory cytokines such as interleukin-1 β (IL-1 β ), Interleukin-6 (IL-6), and tumour necrosis factor- α (TNF- α ). These proinflammatory cytokines are responsible for initiating inflammation in response to tissue injury. Anti-inflammatory cytokines and specific cytokine inhibitors are also released to limit the sustained or excessive inflammatory reactions. In the past decade, intensive research has determined the role of proinflammatory cytokines in development of mucositis. However, a large gap remains in the knowledge of the role of anti-inflammatory cytokines in the setting of chemotherapy-induced mucositis. This critical paper will highlight current literature available relating to what is known regarding the development of mucositis, including the molecular mechanisms involved in inducing inflammation particularly with respect to the role of proinflammatory cytokines, as well as provide a detailed discussion of why it is essential to consider extensive research in the role of anti-inflammatory cytokines in chemotherapy-induced mucositis so that effective targeted treatment strategies can be developed.